2002
DOI: 10.1046/j.1523-1747.2002.19523.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Telomere Lengths and Erosion with Age in Human Epidermis and Lingual Epithelium

Abstract: We investigated progressive telomere shortening in normal human epidermis and lingual epithelium during aging, and attempted, in particular, to ascertain whether the telomere shortening that accompanies aging occurs at the same rate in different tissues. We studied telomeric DNA integrity, and estimated annual telomere loss, in 52 specimens of epidermis and 48 specimens of lingual epithelium collected at autopsy from subjects who had died at ages between 0 and 101 y. Most of the DNA samples were measured twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
2
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 43 publications
(85 reference statements)
5
72
2
1
Order By: Relevance
“…It is important to note that the epidermis is one of the few regenerative tissues to express telomerase [13]. Further, in a recent investigation of progressive telomere shortening, in 52 specimens of normal human epidermis and 48 specimens of lingual epithelium collected at autopsy from subjects who died between 0 and 101 years of age, researchers determined that the telomere shortening associated with ageing is characterized by tissue-specific loss rates [14]. Indeed, the natural, progressive shortening of telomeres may be one of the primary mechanisms of cellular ageing in skin [15].…”
Section: Intrinsic Ageingmentioning
confidence: 99%
“…It is important to note that the epidermis is one of the few regenerative tissues to express telomerase [13]. Further, in a recent investigation of progressive telomere shortening, in 52 specimens of normal human epidermis and 48 specimens of lingual epithelium collected at autopsy from subjects who died between 0 and 101 years of age, researchers determined that the telomere shortening associated with ageing is characterized by tissue-specific loss rates [14]. Indeed, the natural, progressive shortening of telomeres may be one of the primary mechanisms of cellular ageing in skin [15].…”
Section: Intrinsic Ageingmentioning
confidence: 99%
“…For other taxa, telomere dynamics have generally not been investigated in epidermis samples, but in blood samples (Monaghan and Haussmann, 2006), with some exceptions in humans (e.g. Nakamura et al, 2002;Sugimoto et al, 2006). Significant correlations were found between telomere lengths in different tissues within individual humans Takubo et al, 2002).…”
mentioning
confidence: 99%
“…Similarly, another study conducted on newborns found a strong correlation (r =.89) between TL of white blood cells and TL of umbilical artery cells [43]. And in two post-mortem samples of 41 and 21 subjects from 0 to 101 years of age, Nakamura reported significant associations in lingual epithelium cell TL and epidermis TL (r =.84 and r =.93, respectively) [42]. By additionally controlling for donor age, Friedrich and colleagues found significant correlations in tissue samples from 9 patients (age 75-95 years) between epidermis TL and leukocyte TL (R2 =.79), epidermis TL and synovial sample TL (R 2 =.71), and synovial sample TL and leukocyte TL (R 2 =.54) [45].…”
Section: Telomeres In Different Tissuesmentioning
confidence: 77%
“…So far, only few studies have compared TL concordance across different tissues [40][41][42][43][44][45], and to date no study observed TL dynamics in different tissue samples across multiple time points to compare TL dynamics between tissues over time. Still, some cross-sectional studies report synchrony over different tissues.…”
Section: Telomeres In Different Tissuesmentioning
confidence: 99%